Effect of pH on the toxicity of fumonisins towards the RTL-W1 cell line and zebrafish (Danio rerio) embryos - Plessis, Belinda du; Regnier, Thierry; Combrinck, Sandra; Heinrich, Patrick; Braunbeck, Thomas (Toxicology letters, 2019)
Fumonisins are common contaminants of maize. The neutral red assay, using the RTL-W1 trout liver cell line, and the fish embryo test (FET), using zebrafish, were selected to assess the effect of pH on the cytotoxicity, acute toxicity and teratogenicity of fumonisin B1 (FB1). The results demonstrated that FB1 exerts low cytotoxicity towards RTL-W1 cells without pH adjustment (IC50 1 746μM), and no cytotoxicity after pH-adjustment to physiological conditions. The LC50 value for FB1 in the FET (1 058μM at 48h) confirmed low acute toxicity. Adjusting the pH to physiological conditions reduced the acute toxicity of FB1 towards zebrafish embryos, emphasising the importance of acidity/basicity of the medium in toxicity testing. Hydrolysed FB1 was less toxic than FB1 (LC50 2 690μM at 48h), and neither were teratogenic towards zebrafish embryos. Results confirm that the FET may account for effects not observable in cell cultures.